Effects of pretreatment methods on biomethane production kinetics and microbial community by solid state anaerobic digestion of sugarcane trash. (May 2022) - Ketsub, Napong; Whatmore, Paul; Abbasabadi, Mahsa; Doherty, William O.S.; Kaparaju, Prasad; O'Hara, Ian M.; Zhang, Zhanying
Graphical abstract: Highlights: Modified Gompertz's model fitted solid state AD (SS-AD) kinetics with cane trash. Pretreatment type affected microbial community and dynamics in SS-AD. Key microbial communities responding to pretreatment type were identified. Bacterial community was significantly related with volatile acids and pretreatment. Archaeal community was significantly related with methane production. Abstract: Solid state anaerobic digestion (SS-AD) of lignocellulose is effective in improving biomethane productivity but is limited by low biomass digestibility and lack of substrate-specific working microorganisms. In this study, the effects of different pretreatment methods on biomethane production by SS-AD of sugarcane trash were studied. The biomethane production, fitted to a modified Gompertz's model, predicted a maximum methane yield of 214.2 L/kg volatile solids (VS) and productivity of 6.9 L/kg VS/day from KOH-pretreated trash, respectively. Microbial community analysis showed that bacterial community was significantly associated with volatile acids and pretreatment types while archaeal community was significantly associated with methane yield. Microbial community dynamics was revealed in SS-AD. Main genera related to pretreatment method were identified and discussed. This study generated important information on SS-AD of lignocellulosic biomass pretreated by different methods, which is useful for developing bioaugmentation strategies to improve biomethane production by SS-AD.